STAR-Vote: A Secure, Transparent, Auditable, and Reliable Voting System - Bell, Susan; Benaloh, Josh; Byrne, Michael D.; DeBeauvoir, Dana; Eakin, Bryce; Fisher, Gail; Kortum, Philip; McBurnett, Neal; Montoya, Julian; Parker, Michelle; Pereira, Olivier; Stark, Philip B.; et al. (USENIX Journal of Election Technology and Systems (JETS), 2013)
STAR-Vote is a collaboration between a number of academics and the Travis County (Austin), Texas elections office, which currently uses a DRE voting system and previously used an optical scan voting system. STAR-Vote represents a rare opportunity for a variety of sophisticated technologies, such as end-to-end cryptography and risk limiting audits, to be designed into a new voting system, from scratch, with a variety of real world constraints, such as election-day vote centers that must support thousands of ballot styles and run all day in the event of a power failure. This paper describes the current design of STAR-Vote which is now largely settled and whose development will soon begin.